Opportunities for smallholder farmers to benefit from conservation agricultural practices - Nhamo, N.; Lungu, O.N. (Elsevier, 2017)
Conservation agriculture (CA) practices combine the use of soil cover, crop combinations, and reduced tillage. There has been widespread promotion of CA practices in southern Africa. The aim of this chapter is to take stock of the advances in understanding the CA systems and to define the benefits of CA to smallholder farmers and where it can best be applied. Research results have shown an improved understanding of how the systems impact production potential and an indicative direction of where the systems may work and where challenges lie. Given the changes in climate and the challenges with soils that may not respond to soil amendments, it is important to define boundary conditions under which CA techniques will deliver on improving production and at the same time mitigate the effects of climate change through improved resource use efficiency.